2023
DOI: 10.3389/fpubh.2023.1065368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of #PsychTwitter in promoting global psychiatry: A hashtag analysis study

Abstract: IntroductionMultiple studies have shown how valuable Twitter hashtags can be for promoting content related to different themes in the online community. This arena has grown into a rich data source for public health observation and understanding key trends in healthcare on a global scale. In the field of mental health in particular, it would be of benefit to understand and report the key stakeholders' (individual mental health professionals, academic organizations and their countries) trends and patterns of psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Concerning the locations of the users who shared #NutritionFactscontaining tweets in the study period (Table 1), not surprising in the top three were countries with big share of English-speaking population (The United States of America, India, and Canada), while it is also interesting to note the presence of users from different continents (North America, Asia, Africa; Table 1), underscoring the broad international interest toward evidence-based nutrition information. Similar patterns of geolocation-distributions with big share of participants from English-speaking countries but also broad international participation were also observed upon analysis of other hashtags with biomedical significance on X, such as #MedTwitterAI and #PsychTwitter (26,34).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Concerning the locations of the users who shared #NutritionFactscontaining tweets in the study period (Table 1), not surprising in the top three were countries with big share of English-speaking population (The United States of America, India, and Canada), while it is also interesting to note the presence of users from different continents (North America, Asia, Africa; Table 1), underscoring the broad international interest toward evidence-based nutrition information. Similar patterns of geolocation-distributions with big share of participants from English-speaking countries but also broad international participation were also observed upon analysis of other hashtags with biomedical significance on X, such as #MedTwitterAI and #PsychTwitter (26,34).…”
Section: Discussionsupporting
confidence: 67%
“…Thus, it is apparent that information associated with the #NutritionFacts tweets is notably advocated at organizational level. For comparison, doctors were previously found to be the leading stakeholder sharing tweets mentioning #SaludTues (hashtag advocating for Latinx health equity) ( 38 ) and #PsychTwitter (hashtag aimed for the dissemination of psychiatric knowledge and information) ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the features on Twitter, that is, "hashtag," connects users to varied topics that they can follow based on interest under an umbrella designated by a name, irrespective of who is making the post [19]. Research has shown the value of hashtags for promoting diverse health-related themes or events such as conferences, chats, and journal clubs [20][21][22][23]. A recent analysis of tweets containing the hashtag #PsychTwitter from 2019 to 2022 shows the massive impact of a hashtag when it is used on a global scale [21]; the #PsychTwitter resulted in 125,297 tweets and 492,565,230 impressions, with the United States being the top country with the most users.…”
Section: Insightsmentioning
confidence: 99%
“…Research has shown the value of hashtags for promoting diverse health-related themes or events such as conferences, chats, and journal clubs [20][21][22][23]. A recent analysis of tweets containing the hashtag #PsychTwitter from 2019 to 2022 shows the massive impact of a hashtag when it is used on a global scale [21]; the #PsychTwitter resulted in 125,297 tweets and 492,565,230 impressions, with the United States being the top country with the most users. While most published studies on hashtags have explored the role of social media as a platform for providing support and information about varying health topics, there is limited research addressing engagement performance (eg, number of impressions or tweets) with certain hashtags.…”
Section: Insightsmentioning
confidence: 99%